MODUS DAN INFERENSI DALAM TEKS LAGU JAWA KARYA DIDI KEMPOT - Setiyadi, Dwi Bambang Putut; Herawati, Nanik (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
The research objective is to describe the mood and inference in the Javanese song text by Didi Kempot. Mood is the expression of the speaker’s attitude towards what he says. Inference is a process that must be carried out by the communicant to understand the meaning not contained in the discourse. Discourse that uses various modes is multimodal text. Multimodal text is not just text in written form, but also written text accompani edaudiovisual text or verbal and audiovisual text. The research strategy used is qualitative research. Data collection techniques using document techniques and audiovisual materials. Document technique to obtain data about Didi Kempot's curriculum vitae and album. The audiovisual material technique is to find data from albums on CDs and the internet, especially You Tube. The triangulation technique uses data triangulation, theory, method, and data. Data analysis techniques use interactive analysis models: reduce data, present data, and draw conclusions. The results of the research on Javanese song texts by Didi Kempot contained indicative, optative, negative, interrogative, and imperative modes. The most used mood is the indicative mode. Based on the situation and cultural context, it is concluded that Didi Kempot had experienced a bitter experience in love that made his heart languish. This can be seen from the overall meaning of the texts of the Javanese songs written by Didi Kempot, which generally tell about feelings of sadness and heartbreak because they are abandoned by their loved ones.Tujuan penelitian ini mendeskripsikan modus dan inferensi dalam teks lagu Jawa karya Didi Kempot. Modus merupakan pengungkapan sikap penutur terhadap apa yang dituturkannya. Inferensi adalah proses yang harus dilakukan oleh komunikan untuk memahami makna yang tidak terdapat dalam wacana. Wacana yang menggunakan berbagai moda disebut taks multimodal. Teks multimodal bukan hanya sebuah teks yang berbentuk tulisan saja, melainkan juga teks tulis yang disertai teks audiovisual atau teks verbal dan audiovisual. Penelitian ini adalah penelitian kualitatif. Pengumpulan data menggunakan teknik dokumen untuk mendapatkan data-data riwayat hidup dan albu-album Didi Kempot serta teknik materi audiovisual untuk mencari data-data dari album CD dan You Tube. Validitas menggunakan triangulasi data, teori, metode, dan peneliti. Teknik analisis data menggunakan analisis interaktif: mereduksi data, menyajikan data, dan menarik kesimpulan. Hasil penelitian terhadap teks lagu Jawa karya Didi Kempot memperlihatkan adanya modus indikatif, optatif, negatif, interogatif, dan imperatif. Modus terbanyak adalah modus indikatif. Hasil kajian terhadap inferensi teks menghasilkan pengalaman pahit dalam cinta yang membuat seseorang merana. Hal ini terlihat dari keseluruhan makna teks lagu-lagu karya Didi Kempot yang pada umumnya berkisah tentang perasaan sedih dan patah hati karena ditinggalkan kekasihnya.